El derecho de mantener una familia en reproduccion asistida en parejas lesbianas - Arteaga Naranjo, Mónica (2019)
Within our thesis project we have been good at explaining the need for reform and recognition of homoparental families, in this case within lesbian couples, our country is a country that guarantees rights and protects the family, but does not is reflected that there are different types of families, with the continuous evolution that exists in the world, it would be illogical not to modify our laws. Within this project we will talk about the different types of family that exist today, as well as the scientific methods that can be used for the procreation of a new being, who will be the couple's son…..